2011
DOI: 10.1002/jmr.1113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the beta‐sheet‐breaker peptide LPFFD on oriented network of amyloid β25‐35 fibrils

Abstract: Amyloid fibrils are self-associating filamentous structures deposited in extracellular tissue in various neurodegenerative and protein misfolding disorders. It has been shown that beta-sheet-breaker (BSB) peptides may interfere with amyloid fibril assembly. Although BSB peptides are prospective therapeutic agents in amyloidosis, there is ambiguity about the mechanisms and generality of their action. In the present work we analyzed the effect of the BSB peptide LPFFD on the growth kinetics, morphologic, and mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…7 D). Our results are analogous to the peeling of amyloid protofilaments away from the bundles by dismantling side-by-side associations (see, e.g., Kellermayer and colleagues (54)(55)(56)), but in our case, the fibrils are embedded in a gel matrix with junction zones of varying strengths. Note that long force steps can arise due to desorption of fibrils from the substrate in a train conformation (see, e.g., (57)(58)(59)(60)(61)).…”
Section: Hierarchical Force Staircases As a Mechanical Signature Of The Gel Networksupporting
confidence: 77%
“…7 D). Our results are analogous to the peeling of amyloid protofilaments away from the bundles by dismantling side-by-side associations (see, e.g., Kellermayer and colleagues (54)(55)(56)), but in our case, the fibrils are embedded in a gel matrix with junction zones of varying strengths. Note that long force steps can arise due to desorption of fibrils from the substrate in a train conformation (see, e.g., (57)(58)(59)(60)(61)).…”
Section: Hierarchical Force Staircases As a Mechanical Signature Of The Gel Networksupporting
confidence: 77%
“…Inspired by the way biological systems harness multivalent molecular interactions, 25−27 mPPCs consist of a hydrophilic polymer backbone bearing multiple copies of the "β-breaker" peptide LPFFD. 28,29 In previous works, it was shown that mPPCs can modulate both the growth and stability of amyloid, inhibiting the formation of Aβ 40 fibrils 13,23 and breaking down preformed Aβ 40 fibrils into sub-100-nm structures. 16 By virtue of their multivalency, mPPCs achieve significantly higher inhibition and disassembly efficacy than corresponding amounts of monomeric LPFFD.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Currently, several types of inhibitors that target amyloid aggregation are under development, including small molecule inhibitors, peptides, nanoparticles, antibodies, and proteins . Among them, peptides and peptidomimetics have been extensively studied for their specific interactions with Aβ .…”
Section: Introductionmentioning
confidence: 99%